Preparation method of three-phase NaxMnyNizFewCuvO2 oxide sodium ion battery positive electrode material

Through a multi-factor coordination method, the P2/O3/β three-phase composite material of the positive electrode material of sodium oxide ion battery is directionally synthesized, solving the problem of random composite phase formation and improving the electrochemical performance and cyclic stability of the material.

CN119627093APending Publication Date: 2025-03-14SICHUAN VOCATIONAL & TECHN COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411712495.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The composite phase formation of existing sodium oxide battery positive electrode materials is randomly formed during the synthesis process, making it difficult to regulate the phase ratio, affecting the electrochemical performance of the material.

Method used

By controlling the proportion of active elements (Mn, Ni, Fe), selecting the source of reactant Mn, introducing specific doping elements, adjusting sodium content and controlling reaction conditions (temperature, calcining time and cooling rate), the target P2/O3/β three-phase composite material is achieved.

Benefits of technology

The P2/O3/β three-phase composite material was successfully prepared, which significantly improved the charge and discharge specific capacity and cycle stability, made full use of the advantages of the redox pair, and enhanced the structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627093A_ABST
    Figure CN119627093A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a three-phase NaxMnyNizFewCuvO2 oxide sodium ion battery positive electrode material, and belongs to the technical field of energy storage materials. According to the method, the proportion control of active elements (Mn, Ni and Fe), the selection of a reactant Mn source, the induction of a specific doping element, the adjustment of the sodium content and the accurate regulation and control of reaction conditions (temperature, calcination time and cooling rate) are adopted, the accurate design of a composite phase material composed of specific phases is carried out, and the synthesis of the P2 / O3 / beta three-phase composite material NaxMnyNizFewCuvO2 is successfully realized. Moreover, through accurate stoichiometric design, the three-phase composite material fully utilizes the advantages of specific redox pairs in each phase, the ultrahigh electrochemical performance is realized, the powerful interlocking effect is realized by the three structures, the phase change and the unit cell volume change in the cycle process are effectively inhibited, and the material has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high performance multiphase Na x Mn y Ni z Fe w Cu v The invention relates to a method for preparing an O2 oxide sodium ion battery positive electrode material, and belongs to the technical field of energy storage materials. Background Art

[0002] Oxide cathode materials have the advantages of simple preparation, high theoretical specific capacity, and strong controllability, and are one of the most promising cathode materials for sodium-ion batteries. At present, the most widely studied oxide cathode materials are generally Mn-based materials with Ni and Fe as the main elements. These three elements each have obvious electrochemical reaction characteristics and restrict each other in the overall electrochemical reaction. In materials with different structures, the advantages, reaction characteristics and effects of each redox pair are different.

[0003] At present, in addition to the common P2 and O3 type layered oxide materials, multiphase composite materials have become a new research hotspot. As mentioned earlier, different phases are conducive to the best electrochemical performance of specific active elements. Therefore, multiphase composite materials can often combine the advantages of different phases, give full play to the advantages of each redox reaction and structural characteristics, and obtain better electrochemical performance. In addition, by utilizing the asynchrony of the phase change laws of different phases during the electrochemical cycle, the composite phase structure can restrain each other during the phase change process, achieving an "interlocking effect", thereby reducing the phase change and unit cell volume changes during the cycle and improving the structural stability.

[0004] However, the synthesis of composite phase materials is almost random. Although there is guidance from the theory of cation potential, the synthesis of composite phase materials with specific structures and the regulation of the proportion of each phase, especially when there are more than two phases, are still very difficult due to too many influencing factors. Therefore, it is of great significance in the research and development and application of positive electrode materials for oxide sodium ion batteries to study the factors that affect the formation of composite phases and synthesize target composite phase materials by specific means. Summary of the invention

[0005] Aiming at the randomness of composite phase formation in the synthesis process of positive electrode materials for oxide sodium ion batteries, the present invention proposes a method of multi-factor coordination using active element (Mn, Ni, Fe) ratio control, reactant Mn source selection, specific doping element induction, sodium content adjustment, and precise control of reaction conditions (temperature, calcination time, and cooling rate). On the basis of directional control of the formation of a two-phase composite phase and regulation of the two-phase ratio, the target P2 / O3 / β three-phase composite material is successfully prepared, and the factors affecting the formation of multiple phases are summarized, and a directional synthesis method is given. Finally, a P2 / O3 / β three-phase composite material is successfully obtained, which has significantly improved charge and discharge specific capacity and cycle stability.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A three-phase Na x Mn y Ni z Fe w Cu v The preparation method of the positive electrode material of O2 oxide sodium ion battery is carried out according to the following steps:

[0008] Step 1: Weighing and mixing

[0009] (1.1) According to Na x Mn y Ni z Fe w Cu v The stoichiometric ratio of metal cations in O2 is used to weigh out the corresponding mass of various raw materials containing Na, Mn, Ni, Fe, and Cu; among them, the Mn raw material is a mixture of Mn2O3 and MnO2; the source of Cu is CuO;

[0010] (1.2) The weighed raw materials are mixed evenly by ethanol ball milling, and after the ball milling, they are placed in a drying oven for drying;

[0011] Step 2: Sample preparation and calcination

[0012] (2.1) Pressing the mixed and dried raw materials into sheets;

[0013] (2.2) Placing the flake raw material in a muffle furnace, heating it to the sintering temperature at a constant heating rate in an air atmosphere, and then keeping it at this temperature for a certain period of time;

[0014] (2.3) After sintering and heat preservation, cool to room temperature at a certain cooling rate.

[0015] Furthermore, in the first step (1.1), the source of Na is one or a mixture of two or more of Na2CO3, CH3COONa, and NaOH; the source of Ni is one or two of NiO or Ni(OH)2; the source of Fe is one or a mixture of two or more of FeO, Fe2O3, and Fe3O4.

[0016] Furthermore, in (1.1) of the first step, 0.8≤x≤1.0; 0.4≤y≤0.55; 0.2≤z≤0.4; 0.1≤w≤0.3; 0.05≤v≤0.1.

[0017] Furthermore, in the first step (1.1), the atomic ratio of Mn / Ni in the reactants is 1 / 1≤Mn / Ni≤2 / 1.

[0018] Furthermore, in the first step (1.1), the reactants are from Mn2O3 (Mn 3+ ) and MnO2(Mn 4+ ) is 0 <Mn 3+ / Mn 4+ ≤6 / 4.

[0019] Furthermore, in the first step (1.2), the ball milling speed is 300-400 rpm, and the ball milling time is 3-6 h.

[0020] Furthermore, in the second step (2.2), the constant heating rate is 1-10°C / min; the sintering temperature range is 850-980°C; and the holding time is 12-24h.

[0021] Furthermore, in the second step (2.3), the cooling rate to room temperature is 5 to 20°C / min.

[0022] The design concept of the present invention: Combining a large number of previous research results and our experimental verification, the present invention proposes a multi-factor coordinated method of synthesizing the target multiphase material by controlling the proportion of active elements (Mn, Ni, Fe), selecting the reactant Mn source, inducing specific doping elements, adjusting the sodium content, and precisely controlling the reaction conditions (temperature, calcination time, and cooling rate). In the induction process of P2 / O3 / β three-phase material, the control of the above-mentioned multiple conditions is utilized. The specific ideas and steps are as follows: 1) Provide the prerequisite for the formation of multiphase composite materials by regulating the sodium content; 2) Control the Mn / Ni ratio and Fe content to achieve the formation of P2 / O3 composite phase and the regulation of the two-phase ratio; 3) Create conditions for the formation of β phase in air atmosphere by appropriate Cu doping; 4) Control the formation and content of β phase in the product by controlling the Mn source in the reactant; 5) Control the chemical reaction process by controlling the reaction temperature and calcination time, thereby affecting the product structure; 6) Control the element valence and structural changes that occur during the cooling process by controlling the cooling rate after calcination, control the average valence state of the valence-changing elements (mainly Mn) in the structure, and then control its influence on the structure. Through the precise regulation of the control variables of the above factors and through a large number of experiments, the target P2 / O3 / β three-phase composite material was finally successfully synthesized. The precise element ratio design enables the obtained three-phase composite material to fully utilize the advantages of redox pairs in different structures, significantly improving the capacity of the material. At the same time, the enhanced interlocking effect greatly improves the material's cycle capacity retention rate. In addition, in order to prove the necessity of the conditions in the claims, we set up a series of comparative experiments, all of which generated single-phase or dual-phase materials.

[0023] Beneficial effects of the present invention:

[0024] 1. The factors affecting the formation of composite materials are summarized, and a series of methods for controlling the synthesis of composite materials are given to provide guidance for the synthesis of composite materials;

[0025] 2. Based on the previous two-phase materials, through more precise multi-factor control, the P2 / O3 / β three-phase material was synthesized for the first time, further improving the electrochemical performance of the material;

[0026] 3. Through the precise design of element stoichiometry, each active redox pair is fully utilized in different phase components, which enables the composite phase material to obtain excellent electrochemical properties;

[0027] 4. The interlocking effect gained by the three-phase composite material improves the cyclic stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1aThis is the first charge and discharge curve of the sample provided in Example 1 of the present invention at 25°C. In the figure, the horizontal axis Capacity represents the discharge specific capacity (mA hg -1 ), the vertical axis Voltage represents voltage (V).

[0029] Figure 1b This is a cycle capacity diagram of the sample provided in Example 1 of the present invention at 25°C. In the figure, the horizontal axis Cyclenumber represents the number of cycles, and the vertical axis Capacity represents the specific capacity (mAhg -1 ).

[0030] Figure 2a This is the first charge and discharge curve of the sample provided in Example 2 of the present invention at 25°C. In the figure, the horizontal axis Capacity represents the discharge specific capacity (mA hg -1 ), the vertical axis Voltage represents voltage (V).

[0031] Figure 2b This is a cycle capacity diagram of the sample provided in Example 2 of the present invention at 25°C. In the figure, the horizontal axis Cyclenumber represents the number of cycles, and the vertical axis Capacity represents the specific capacity (mAhg -1 ).

[0032] Figure 3a This is the first charge and discharge curve of the sample provided in Example 3 of the present invention at 25°C. In the figure, the horizontal axis Capacity represents the discharge specific capacity (mAh g -1 ), the vertical axis Voltage represents voltage (V).

[0033] Figure 3b This is a cycle capacity diagram of the sample provided in Example 3 of the present invention at 25°C. In the figure, the horizontal axis Cyclenumber represents the number of cycles, and the vertical axis Capacity represents the specific capacity (mAhg -1 ).

[0034] Figure 4a This is the first charge and discharge curve of the sample provided in Comparative Example 1 of the present invention at 25°C. In the figure, the abscissa Capacity represents the discharge specific capacity (mAh g -1 ), the vertical axis Voltage represents voltage (V).

[0035] Figure 4b This is a cycle capacity diagram of the sample provided in Comparative Example 1 of the present invention at 25°C. In the figure, the abscissa Cyclenumber represents the number of cycles, and the ordinate Capacity represents the specific capacity (mAhg -1 ).

[0036] Figure 5a This is the first charge and discharge curve of the sample provided in Comparative Example 2 of the present invention at 25°C. In the figure, the horizontal axis Capacity represents the discharge specific capacity (mAh g -1 ), the vertical axis Voltage represents voltage (V).

[0037] Figure 5b This is a cycle capacity diagram of the sample provided in Comparative Example 2 of the present invention at 25°C. In the figure, the abscissa Cyclenumber represents the number of cycles, and the ordinate Capacity represents the specific capacity (mAhg -1 ).

[0038] Figure 6a This is the first charge and discharge curve of the sample provided in Comparative Example 3 of the present invention at 25°C. In the figure, the abscissa Capacity represents the discharge specific capacity (mAh g -1 ), the vertical axis Voltage represents voltage (V).

[0039] Figure 6b This is a cycle capacity diagram of the sample provided in Comparative Example 3 of the present invention at 25°C. In the figure, the abscissa Cyclenumber represents the number of cycles, and the ordinate Capacity represents the specific capacity (mAhg -1 ).

[0040] Figure 7a This is the first charge and discharge curve of the sample provided in Comparative Example 4 of the present invention at 25°C. In the figure, the abscissa Capacity represents the discharge specific capacity (mAh g -1 ), the vertical axis Voltage represents voltage (V).

[0041] Figure 7b This is a cycle capacity diagram of the sample provided in Comparative Example 4 of the present invention at 25°C. In the figure, the horizontal axis Cyclenumber represents the number of cycles, and the vertical axis Capacity represents the specific capacity (mAhg -1 ).

[0042] Figure 8a This is the first charge and discharge curve of the sample provided in Comparative Example 5 of the present invention at 25°C. In the figure, the abscissa Capacity represents the discharge specific capacity (mAh g -1 ), the vertical axis Voltage represents voltage (V).

[0043] Figure 8b This is a cycle capacity diagram of the sample provided in Comparative Example 5 of the present invention at 25°C. In the figure, the abscissa Cyclenumber represents the number of cycles, and the ordinate Capacity represents the specific capacity (mAhg -1 ). DETAILED DESCRIPTION

[0044] In the specific implementation process, in order to directionally synthesize the target multiphase composite material, the present invention regulates and changes the ratio of active elements (Mn, Ni, Fe), reactant Mn source, doping elements, sodium content and reaction conditions according to the scheme given in the claims, and controls Cu doping and reactant Mn source on the basis of controlling the content and ratio of the three active elements to induce P2 / O3 two-phase material, further induces β-phase structure, and finally synthesizes P2 / O3 / β three-phase composite material.

[0045] Furthermore, in order to prove the necessity of the conditions given in the above claims, a series of comparative examples are set up, which all implement single variable control relative to the embodiments.

[0046] The experimental methods described in the following examples are conventional methods unless otherwise specified. The reagents and materials described are commercially available unless otherwise specified.

[0047] Example 1

[0048] In this embodiment, a high performance P2 / O3 / β-Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 The preparation method of the oxide positive electrode material of an O2 sodium ion battery comprises the following steps:

[0049] Step 1: Weighing and mixing

[0050] (1) According to Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 The stoichiometric ratio of metal cations in O2 is used to weigh the corresponding masses of Na2CO3, MnO2, Mn2O3, NiO, Fe2O3 and CuO, among which Mn in the reactant is 3+ (from Mn2O3) and Mn 4+ The ratio (from MnO2) is 5 / 5.

[0051] (2) The weighed raw materials were ball-milled at 350 rpm for 5 h to mix evenly, and then placed in a drying oven for drying after ball-milling;

[0052] Step 2: Sample preparation and sintering

[0053] (1) Pressing the mixed raw materials into sheets;

[0054] (2) placing the bulk raw material in a muffle furnace, heating the temperature to 950°C at a rate of 5°C / min in an air atmosphere, and maintaining the temperature at this temperature for 15 h;

[0055] (3) After sintering and heat preservation is completed, the temperature is lowered to room temperature at a rate of 10°C / min.

[0056] like Figure 1a As shown, the synthesized P2 / O3 / β-Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 O2 cathode material in the voltage range of 2.0–4.0V, 75mAg -1 The half-cell charge and discharge test was carried out at a current density of 1.5 %. From the first charge and discharge curve of the sample at 25 °C, it can be seen that the first charge specific capacity is 150.2 mAh g -1 The first discharge capacity is 181.8 mAh g -1 .from Figure 1b From the graph of the change of cycle capacity with the number of cycles, it can be seen that the capacity retention rate is 89.7% after 100 cycles.

[0057] Example 2

[0058] In this embodiment, a high performance P2 / O3 / β-Na 0.8 Mn 0.4 Ni 0.2 Fe 0.3 Cu 0.1 The preparation method of the oxide positive electrode material of an O2 sodium ion battery comprises the following steps:

[0059] Step 1: Weighing and mixing

[0060] (1) According to Na 0.8 Mn 0.4 Ni 0.2 Fe 0.3 Cu 0.1 The stoichiometric ratio of metal cations in O2 is used to weigh out the corresponding masses of NaOH, MnO2, Mn2O3, Ni(OH)2, Fe3O4 and CuO, where Mn in the reactant is 3+ (from Mn2O3) and Mn 4+ The ratio (from MnO2) is 2 / 8.

[0061] (2) The weighed raw materials were ball-milled at 300 rpm for 6 h to mix evenly, and then placed in a drying oven for drying after ball-milling;

[0062] Step 2: Sample preparation and sintering

[0063] (1) Pressing the mixed raw materials into sheets;

[0064] (2) placing the bulk raw material in a muffle furnace, heating the temperature to 900°C at a rate of 1°C / min in an air atmosphere, and maintaining the temperature at this temperature for 18 h;

[0065] (3) After sintering and heat preservation is completed, the temperature is lowered to room temperature at a rate of 5°C / min.

[0066] like Figure 2a As shown, the synthesized P2 / O3 / β-Na 0.8 Mn 0.4 Ni 0.2 Fe 0.3 Cu 0.1 O2 cathode material in the voltage range of 2.0–4.0V, 75mAg -1 The half-cell charge and discharge test was carried out at a current density of 1.34 Å. From the first charge and discharge curve of the sample at 25 °C, it can be seen that the first charge specific capacity is 111.8 mAh g -1 The first discharge capacity is 153.0 mAh g -1 .from Figure 2b From the graph of the change of cycle capacity with the number of cycles, it can be seen that the capacity retention rate is 94.0% after 100 cycles.

[0067] Example 3

[0068] In this embodiment, a high performance P2 / O3 / β-NaMn 0.55 Ni 0.3 Fe 0.1 Cu 0.05 The preparation method of the oxide positive electrode material of an O2 sodium ion battery comprises the following steps:

[0069] Step 1: Weighing and mixing

[0070] (1) According to NaMn 0.55 Ni 0.2 Fe 0.2 Cu 0.05 The stoichiometric ratio of metal cations in O2 is used to weigh the corresponding masses of Na2CO3, MnO2, Mn2O3, Ni(OH)2, FeO and CuO, among which Mn in the reactant is 3+ (from Mn2O3) and Mn 4+ The ratio (from MnO2) is 6 / 4.

[0071] (2) The weighed raw materials were ball-milled at 400 rpm for 4 h to mix evenly, and then placed in a drying oven for drying after ball-milling;

[0072] Step 2: Sample preparation and sintering

[0073] (1) Pressing the mixed raw materials into sheets;

[0074] (2) placing the bulk raw material in a muffle furnace, heating the temperature to 850°C at a rate of 10°C / min in an air atmosphere, and maintaining the temperature at this temperature for 24 hours;

[0075] (3) After sintering and heat preservation is completed, the temperature is lowered to room temperature at a rate of 20°C / min.

[0076] like Figure 3a As shown, the synthesized P2 / O3 / β-NaMn 0.55 Ni 0.2 Fe 0.2 Cu 0.05 O2 cathode material in the voltage range of 2.0–4.0V, 75mAg -1 The half-cell charge and discharge test was carried out at a current density of 1.5 %. From the first charge and discharge curve of the sample at 25°C, it can be seen that the first charge specific capacity is 131.0 mA hg -1 The first discharge capacity is 169.5 mAh g -1 .from Figure 3b From the graph of the change of cycle capacity with the number of cycles, it can be seen that the capacity retention rate is 91.5% after 100 cycles.

[0077] Comparative Example 1

[0078] In this comparative example, the doping amount of Cu was reduced to synthesize P2 / O3-Na 0.88 Mn 0.5 Ni 0.255 Fe 0.225 Cu 0.02 O2 sodium ion battery oxide positive electrode material, comprising the following steps:

[0079] Step 1: Weighing and mixing

[0080] (1) According to Na 0.88 Mn 0.5 Ni 0.255 Fe 0.225 Cu 0.02 The stoichiometric ratio of metal cations in O2 is used to weigh the corresponding masses of Na2CO3, MnO2, Mn2O3, NiO, Fe2O3 and CuO, among which Mn in the reactant is 3+ (from Mn2O3) and Mn 4+ The ratio (from MnO2) is 5 / 5.

[0081] (2) The weighed raw materials were ball-milled at 350 rpm for 5 h to mix evenly, and then placed in a drying oven for drying after ball-milling;

[0082] Step 2: Sample preparation and sintering

[0083] (1) Pressing the mixed raw materials into sheets;

[0084] (2) placing the bulk raw material in a muffle furnace, heating the temperature to 950°C at a rate of 5°C / min in an air atmosphere, and maintaining the temperature at this temperature for 15 h;

[0085] (3) After sintering and heat preservation is completed, the temperature is lowered to room temperature at a rate of 10°C / min.

[0086] like Figure 4a As shown, the synthesized P2 / O3-Na 0.88 Mn 0.5 Ni 0.255 Fe 0.225 Cu 0.02 O2 cathode material in the voltage range of 2.0–4.0V, 75mAg -1 The half-cell charge and discharge test was carried out at a current density of 1.34 Å. From the first charge and discharge curve of the sample at 25 °C, it can be seen that the first charge specific capacity is 112.7 mAh g -1 The first discharge capacity is 134.8 mAh g -1 .from Figure 4b From the graph of the change of cycle capacity with the number of cycles, it can be seen that the capacity retention rate is 76.1% after 100 cycles.

[0087] Comparative Example 2

[0088] In this comparative example, only a single Mn2O3 was used as the reaction Mn source to synthesize the P2 / O3 dual-phase Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 O2 sodium ion battery oxide positive electrode material, comprising the following steps:

[0089] Step 1: Weighing and mixing

[0090] (1) According to Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 The stoichiometric ratio of the metal cations in O2 is used to weigh out the corresponding masses of Na2CO3, Mn2O3, NiO, Fe2O3 and CuO.

[0091] (2) The weighed raw materials were ball-milled at 350 rpm for 5 h to mix evenly, and then placed in a drying oven for drying after ball-milling;

[0092] Step 2: Sample preparation and sintering

[0093] (1) Pressing the mixed raw materials into sheets;

[0094] (2) placing the bulk raw material in a muffle furnace, heating the temperature to 950°C at a rate of 5°C / min in an air atmosphere, and maintaining the temperature at this temperature for 15 h;

[0095] (3) After sintering and heat preservation is completed, the temperature is lowered to room temperature at a rate of 10°C / min.

[0096] like Figure 5a As shown, the synthesized P2 / O3-Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 O2 cathode material in the voltage range of 2.0–4.0V, 75mAg -1 The half-cell charge and discharge test was carried out at a current density of 1.5 %. From the first charge and discharge curve of the sample at 25°C, it can be seen that the first charge specific capacity is 123.6 mA hg -1 The first discharge capacity is 134.2mA hg -1 .from Figure 5b From the graph of the change of cycle capacity with the number of cycles, it can be seen that the capacity retention rate is 87.3% after 100 cycles.

[0097] Comparative Example 3

[0098] In this comparative example, Cu was not used, and the doping element was changed to Mg to synthesize P2 / O3 dual-phase Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Mg 0.1 O2 sodium ion battery oxide positive electrode material, comprising the following steps:

[0099] Step 1: Weighing and mixing

[0100] (1) According to Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Mg 0.1 The stoichiometric ratio of metal cations in O2 is used to weigh the corresponding masses of Na2CO3, MnO2, Mn2O3, NiO, Fe2O3 and MgO, among which Mn in the reactant is 3+ (from Mn2O3) and Mn 4+ The ratio (from MnO2) is 5 / 5.

[0101] (2) The weighed raw materials were ball-milled at 350 rpm for 5 h to mix evenly, and then placed in a drying oven for drying after ball-milling;

[0102] Step 2: Sample preparation and sintering

[0103] (1) Pressing the mixed raw materials into sheets;

[0104] (2) placing the bulk raw material in a muffle furnace, heating the temperature to 950°C at a rate of 5°C / min in an air atmosphere, and maintaining the temperature at this temperature for 15 h;

[0105] (3) After sintering and heat preservation is completed, the temperature is lowered to room temperature at a rate of 10°C / min.

[0106] like Figure 6a As shown, the synthesized P2 / O3-Na 0.88 Mn 0.5 Ni 0.255 Fe 0.145 Mg 0.1 O2 cathode material in the voltage range of 2.0–4.0V, 75mAg -1 The half-cell charge and discharge test was carried out at a current density of 1.38 Å. From the first charge and discharge curve of the sample at 25°C, it can be seen that the first charge specific capacity is 119.0 mA hg -1 The first discharge capacity is 136.4 mA hg -1 .from Figure 6b From the graph of the change of cycle capacity with the number of cycles, it can be seen that the capacity retention rate is 82.7% after 100 cycles.

[0107] Comparative Example 4

[0108] In this comparative example, the content of Na was changed to 0.67, and a single P2 phase oxide positive electrode material Na 0.67 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 O2, including the following steps:

[0109] Step 1: Weighing and mixing

[0110] (1) According to Na 0.67 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 The stoichiometric ratio of metal cations in O2 is used to weigh the corresponding masses of Na2CO3, MnO2, Mn2O3, NiO, Fe2O3 and CuO, among which Mn in the reactant is 3+ (from Mn2O3) and Mn 4+ The ratio (from MnO2) is 5 / 5.

[0111] (2) The weighed raw materials were ball-milled at 350 rpm for 5 h to mix evenly, and then placed in a drying oven for drying after ball-milling;

[0112] Step 2: Sample preparation and sintering

[0113] (1) Pressing the mixed raw materials into sheets;

[0114] (2) placing the bulk raw material in a muffle furnace, heating the temperature to 950°C at a rate of 5°C / min in an air atmosphere, and maintaining the temperature at this temperature for 15 h;

[0115] (3) After sintering and heat preservation is completed, the temperature is lowered to room temperature at a rate of 10°C / min.

[0116] like Figure 7a As shown, the synthesized P2-Na 0.67 Mn 0.5 Ni 0.255 Fe 0.145 Cu 0.1 O2 cathode material in the voltage range of 2.0–4.0V, 75mAg -1 The half-cell charge and discharge test was carried out at a current density of 2.5 %. From the first charge and discharge curve of the sample at 25°C, it can be seen that the first charge specific capacity is 93.9 mA hg -1 The first discharge capacity is 108.0mA hg -1 .from Figure 7b From the graph of the change of cycle capacity with the number of cycles, it can be seen that the capacity retention rate is 94.3% after 100 cycles.

[0117] Comparative Example 5

[0118] In this comparative example, the Mn / Ni ratio in the reactants was changed to exceed the range given in the claims, and the P2 / β dual-phase material Na 0.88 Mn 0.555 Ni 0.2 Fe 0.145 Cu 0.1 O2, including the following steps:

[0119] Step 1: Weighing and mixing

[0120] (1) According to Na 0.88 Mn 0.555 Ni 0.2 Fe 0.145 Cu 0.1 The stoichiometric ratio of metal cations in O2 is used to weigh the corresponding masses of Na2CO3, MnO2, Mn2O3, NiO, Fe2O3 and CuO, among which Mn in the reactant is 3+ (from Mn2O3) and Mn 4+The ratio (from MnO2) is 5 / 5.

[0121] (2) The weighed raw materials were ball-milled at 350 rpm for 5 h to mix evenly, and then placed in a drying oven for drying after ball-milling;

[0122] Step 2: Sample preparation and sintering

[0123] (1) Pressing the mixed raw materials into sheets;

[0124] (2) placing the bulk raw material in a muffle furnace, heating the temperature to 950°C at a rate of 5°C / min in an air atmosphere, and maintaining the temperature at this temperature for 15 h;

[0125] (3) After sintering and heat preservation is completed, the temperature is lowered to room temperature at a rate of 10°C / min.

[0126] like Figure 8a As shown, the synthesized P2 / β-Na 0.88 Mn 0.555 Ni 0.2 Fe 0.145 Cu 0.1 O2 cathode material in the voltage range of 2.0–4.0 V, 75 mA g -1 The half-cell charge and discharge test was carried out at a current density of 1.34 W. From the first charge and discharge curve of the sample at 25 °C, it can be seen that the first charge specific capacity is 112.0 mAh g -1 The first discharge capacity is 149.9 mAh g -1 .from Figure 8b From the graph of the change of cycle capacity with the number of cycles, it can be seen that the capacity retention rate is 76.1% after 100 cycles.

[0127] Summary: In summary, controlling the Mn / Ni ratio in the reactants, mixing the Mn source in proportion, using specific doping elements and controlling the Na content in a certain range are all necessary conditions for synthesizing three-phase materials. If any of the conditions are not met, three-phase materials cannot be generated. In addition, slight differences in reaction conditions and chemical ratios will significantly affect the electrochemical properties of multiphase materials. The three three-phase composite materials in the examples all have good cycle stability, and the electrochemical reaction characteristics belonging to different phases can be clearly observed in their charge and discharge curves. Among them, the material in Example 1 has the highest first charge and discharge specific capacity, which are 150.2 mAh g -1 and 181.8mAh g -1 , while the material in Example 2 has the best cycle stability, with a capacity retention rate of 94.0% after 100 cycles. Therefore, multiphase composite is an effective method to improve the electrochemical performance of oxide sodium ion battery cathode materials, and directional synthesis of target composite structures is crucial to the performance improvement and practical application of oxide materials.

Claims

1. A three-phase Na x Mn y Ni z Fe w Cu v The method for preparing an O2 oxide sodium ion battery positive electrode material is characterized in that: Follow these steps: Step 1: Weighing and mixing (1.1) According to Na x Mn y Ni z Fe w Cu v The stoichiometric ratio of metal cations in O2 is used to weigh out the corresponding mass of various raw materials containing Na, Mn, Ni, Fe, and Cu; among them, the Mn raw material is a mixture of Mn2O3 and MnO2; the source of Cu is CuO; (1.2) The weighed raw materials are mixed evenly by ethanol ball milling, and after the ball milling, they are placed in a drying oven for drying; Step 2: Sample preparation and calcination (2.1) Pressing the mixed and dried raw materials into sheets; (2.2) Placing the flake raw material in a muffle furnace, heating it to the sintering temperature at a constant heating rate in an air atmosphere, and then keeping it at this temperature for a certain period of time; (2.3) After sintering and heat preservation, cool to room temperature at a certain cooling rate.

2. The preparation method according to claim 1, characterized in that In the first step (1.1), the source of Na is one or a mixture of two or more of Na2CO3, CH3COONa, and NaOH; the source of Ni is one or two of NiO or Ni(OH)2; the source of Fe is one or a mixture of two or more of FeO, Fe2O3, and Fe3O4.

3. The preparation method according to claim 1, characterized in that: In (1.1) of the first step, 0.8≤x≤1.0; 0.4≤y≤0.55; 0.2≤z≤0.4; 0.1≤w≤0.3; 0.05≤v≤0.

1.

4. The preparation method according to claim 1, characterized in that: In the first step (1.1), the atomic ratio of Mn / Ni in the reactants is 1 / 1≤Mn / Ni≤2 / 1.

5. The preparation method according to claim 1, characterized in that: In the first step (1.1), the ratio of Mn atoms from Mn2O3 and MnO2 in the reactants is 0 <Mn 3+ / Mn 4+ ≤6 / 4.

6. The preparation method according to claim 1, characterized in that: In the first step (1.2), the ball milling speed is 300-400 rpm, and the ball milling time is 3-6 h.

7. The preparation method according to claim 1, characterized in that: In the second step (2.2), the constant heating rate is 1-10°C / min; the sintering temperature range is 850-980°C; and the holding time is 12-24h.

8. The preparation method according to claim 1, characterized in that: In the second step (2.3), the cooling rate to room temperature is 5 to 20°C / min.